DNA alterations in blood cells of Channa punctatus after acute exposure to 4-Nonylphenol - SHARMA, MADHU; CHADHA, POOJA; SHARMA, PARDEEP (The Indian Journal of Animal Sciences, 2020)
The DNA damaging effect of 4-nonylphenol was evaluated in blood cells of fish Channa punctatus by using single gel electrophoresis assay (SGEA). Fish were exposed to three sublethal concentrations (0.15 mg/l, 0.31 mg/l and 0.63 mg/l) of 4-NP which were calculated after LC50 determination. Exposure was given for 96 hours and blood sampling was done after 24, 48, 72 and 96 hours. Tail moment (TM), tail intensity (TI), tail length (TL) and olive tail moment (OTM) were used as parameters for assessing DNA damage. Comet assay results indicated significant DNA fragmentation in blood cells of C. punctatus as a significant increase in the values of all parameters was observed when exposured to different concentrations of 4- NP. Highest damage was observed at 24 h of exposure followed by a decrease in value at 48 and 72 h while at 96 h of exposure increase in the value of all the parameters were observed. On the other hand, after exposure to different concentrations highest damage was seen after treatment with 0.31 mg/l of NP. Owing to the results, the blood cells of C. punctatus show great sensitivity for 4-NP and can be used as bio-indicator for genotoxicity testing.